Effect of Compressive Residual Stress on Fatigue Crack Propagation. (2015) - Morikage, Y.; Igi, S.; Oi, K.; Jo, Y.; Murakami, K.; Gotoh, K.
Abstract: Fatigue failures have sometimes taken place in weld joints due to stress concentration and tensile residual stress at the weld toe. Therefore managements of fatigue crack initiation and propagation contribute to the enhancement of the fatigue life of welded steel structures. The hammer peening process is well known as one of methods to improve the fatigue life of weld joints by generating the compressive residual stress field near the weld toe where recognized as the fatigue crack initiation site. With respect to the fatigue life estimation of the welded steel structure which applied the compressive residual stress field near the weld toe, it is important not only fatigue life estimation for the fatigue crack initiation but also that for the fatigue crack propagation. However there is few research work which deal with the fatigue crack estimation in the compressive residual stress field. In this study, mechanism of fatigue crack propagation in the compressive residual stress field was clarified by experimental observation of crack propagation from a surface crack after hammer peening. Morphology of a propagating surface crack in plate and gusset weld joint specimens were measured by the beach mark method. As a result, it was clarified that morphology of surface crack propagated in the compressive residual stress field was different from that in neutral stress filed. And this phenomenon was clearly observed especially under the low stress intensity factor condition.